Russia in the global parliamentary moment, 1905-1918: between a Subaltern Empire and an Empire of Subalterns - Sablin, Ivan (Locating the global, 2020)
Das Kapitel 11 Russia in the Global Parliamentary Moment, 1905-1918: Between a Subaltern Empire and an Empire of Subalterns erschien in Locating the Global auf Seite 257.
Gesehen am 28.06.2021